Self reported prevalence and practices impacting the outcome of non communicable diseases among corporate professional employees in India - Rohin Rameswarapu; R L Lakshman; Sameer Valsangkar (MRIMS Journal of Health Sciences, 2014)
Background: Non communicable diseases account for 63% of the deaths worldwide and 53% of the deaths in India. Occupation in itself is a risk factor for these diseases in addition to being a modifier of the lifestyle, diet practices and physical activity practices. Objectives: To evaluate socio-demographic factors, self reported prevalence of non communicable disease among corporate professional employees and to assess lifestyle practices and occupational risk factors risk factors modifying the risk of non communicable diseases Materials and methods: A cross sectional study was conducted among corporate professional employees across 20 states in India. Responses were obtained after informed consent through a self administered web based questionnaire with answers entered in a backend database. A semi structured questionnaire was administered with the following parts 1) Socio-demographic information 2) Self reported prevalence of non communicable diseases 3) Lifestyle and diet practices 4) Work related factors. Results: A total of 1582 employees consented and participated in the study. The workforce consisted of 1378 (87.1%) males and 204 (12.9%) females. The mean age was 32.88 ± 7.78 years. The commonest non communicable disease was diabetes with 350 (22.2%) reporting it followed by hypertension with 334 (21.1%) reporting it. Practices relating to exercise were moderately satisfactory, snacking was quite prevalent. Among the workers, 23.1% felt pressured, 19.8% faced difficulties in staying calm and 19% felt overburdened due to work. Conclusions: The study evidenced that corporate employees are exposed to behavioral, life style and dietary risk factors for non communicable diseases at a young age group and that emergent measures are required for rational and cost effective prevention of non communicable diseases to reduce the burden of disease and work days lost among this productive population.